Le Surréalisme : la recherche du point suprême - Waldberg, Patrick (Paris : Editions de la Différence, 1999)
Man Ray ; Picabia, Francis ; Aragon, Louis ; Ernst, Max ; Breton, André ; De Chirico, Giorgio ; Masson, Andre ; Miro, Joan ; Tanguy, Yves ; Malkine, Georges ; Giacometti, Alberto ; Magritte, René ; Dali, Salvador ; Moore, Henri ; Musica, Frantisek ; Matta (Roberto Antonio Sebastian Matta Echaurren)
Frans
boek